The Transformation of Traditional Islamic Boarding Schools as the Foundation of Nusantara Islamic Education and the Preservation of Tradition Amidst Educational Modernization - Zaenal Arifin; Mudzakkir Ali; Nanang Nurcholis (The Future of Education Journal, 2025)
Islamic boarding schools (pesantren) are the oldest educational institutions in Indonesia and serve as the main pillar of Nusantara Islam, a model of Islam that is harmonious with local culture. In this era of disruption, pesantren face dual challenges: the demands of formal education standards and the massive wave of digitalization. This research employs a qualitative method with a Literature Review approach, using primary data obtained from scholarly journals, while secondary data refers to sources such as the internet, theses, dissertations, and relevant books. The findings reveal that the existence of traditional pesantren as the cornerstone of Nusantara Islamic Education lies in their ability to maintain moral and intellectual autonomy amidst the forces of modernity. The strategy employed by traditional pesantren in carrying out this collaboration is often referred to in the Islamic jurisprudence maxim: "Al-muhafazhatu ‘ala al-qadimi al-shalih wa al-akhdzu bi al-jadidi al-ashlah" (Preserving the good of old traditions and adopting better new traditions). In conclusion, pesantren, from a genealogical perspective, are highly adaptive educational institutions. The existence of pesantren in the era of globalization greatly depends on their ability to integrate traditional and modern curricula.